It should be the ten thousands
For this case we must simplify the following expression:
![\frac {1} {3} (x- \frac {1} {3}) - \frac {1} {2} (\frac {2} {3} x- \frac {1} {2})](https://tex.z-dn.net/?f=%5Cfrac%20%7B1%7D%20%7B3%7D%20%28x-%20%5Cfrac%20%7B1%7D%20%7B3%7D%29%20-%20%5Cfrac%20%7B1%7D%20%7B2%7D%20%28%5Cfrac%20%7B2%7D%20%7B3%7D%20x-%20%5Cfrac%20%7B1%7D%20%7B2%7D%29)
So, if we apply distributive property to the terms within parentheses we have:
![\frac {1} {3} x- \frac {1} {9} - \frac {2} {6} x + \frac {1} {4} =\\\frac {1} {3} x- \frac {1} {9} - \frac {1} {3} x + \frac {1} {4} =](https://tex.z-dn.net/?f=%5Cfrac%20%7B1%7D%20%7B3%7D%20x-%20%5Cfrac%20%7B1%7D%20%7B9%7D%20-%20%5Cfrac%20%7B2%7D%20%7B6%7D%20x%20%2B%20%5Cfrac%20%7B1%7D%20%7B4%7D%20%3D%5C%5C%5Cfrac%20%7B1%7D%20%7B3%7D%20x-%20%5Cfrac%20%7B1%7D%20%7B9%7D%20-%20%5Cfrac%20%7B1%7D%20%7B3%7D%20x%20%2B%20%5Cfrac%20%7B1%7D%20%7B4%7D%20%3D)
We simplify taking into account that:
- Equal signs are added and the same sign is placed.
- Different signs are subtracted and the major sign is placed.
![- \frac {1} {9} + \frac {1} {4} =\\- \frac {4} {36} + \frac {9} {36} =\\\frac {-4 + 9} {36} =\\\frac {5} {36}](https://tex.z-dn.net/?f=-%20%5Cfrac%20%7B1%7D%20%7B9%7D%20%2B%20%5Cfrac%20%7B1%7D%20%7B4%7D%20%3D%5C%5C-%20%5Cfrac%20%7B4%7D%20%7B36%7D%20%2B%20%5Cfrac%20%7B9%7D%20%7B36%7D%20%3D%5C%5C%5Cfrac%20%7B-4%20%2B%209%7D%20%7B36%7D%20%3D%5C%5C%5Cfrac%20%7B5%7D%20%7B36%7D)
Answer:
![\frac {5} {36}](https://tex.z-dn.net/?f=%5Cfrac%20%7B5%7D%20%7B36%7D)
Answer:
The diagonal is about 14 m
Step-by-step explanation:
A = s^2
98 = s^2
so
s = √98
diagonal c^2 = 98 + 98
c^2 = 196
c = √196
c ≈ 14
Answer:
The diagonal is about 14 m
Answer:
Step-by-step explanation:
sorry i tried my best i think its like a 30
Yes you always do.
eg x - 2 = 8
x - 2 + 2 = 8 + 2
x = 10
if we plug x = 10 into the original equation we se that this fits:-
10 - 2 = 8